PANDEMIC CRISIS: MACROECONOMIC EFFECTS AND REACTION OF ECONOMIC AUTHORITIES - Jakšić, Pavle (Economic Outlook, 2022)
The crisis caused by the pandemic of the Covid-19 virus has affected all aspects of life, and therefore economic activity on both the micro and macro levels. The aim of the paper is to identify the negative consequences of the Pandemic crisis on the economy of global economies. Using the method of analyzing the key macroeconomic parameters of the selected countries, it is possible to compare the intensity of the impact of the aforementioned crisis. Also, by comparing the movement of the value of the gross domestic product during the Global Recession and the Pandemic Crisis, the author intends to compare which crisis had a greater impact on the decline in the value of the mentioned indicator. In addition, the paper also shows the key economic measures undertaken during 2020 and how these measures affected the movement of public debt in relation to the gross domestic product.